THE ROLE OF COMPUTER AND INFORMATION TECHNOLOGY SCIENCE IN DEVELOPED FOREIGN COUNTRIES - Abdurazzakov Ilhom Rustamovich; Feruza Abdusalim qizi Nuraliyeva (Web of Journals Publishing, 2024)
In this article, the history of computer science in foreign countries, teaching experience, its useful aspects, opportunities and advantages of teaching methods for students of informatics and information technologies are widely covered.
Keywords: The history of formation of teaching computer knowledge abroad , computer science in South Korea, USA, England, Norway.